Pembaharuan hukum Islam dan problem otentisitas agama - Fata, Ahmad Khoirul (Sekolah Tinggi Agama Islam Negeri Salatiga, 2013)
Islam is a universal religion. Its validity beyond the boundaries of pace and time, have challenges while confronted to modernity. New issues emerged make legal problems that must be faced by Islam, in this case fiqh, are becoming increasingly complex and require answers that are not easy. Many attempts were made contemporary muslim intellectual response to the challenge. In general, the effort was focused on two of epistemology: contextual interpretation and emphasis on the principle of maslahah. Practically, both the offer did generate a lot of laws in accordance with the present conditions. But apparently, both contain serious problems if not addressed promptly can undermine the foundations of religion that threatens the authenticity of Islam as a religion of revelation